Proceso de ASC - CIUDADES INTELIGENTES, CONTROL E INTERACTIVIDAD. ANALISIS DESDE LA CONTABILIDAD CRITICA (2023)
In the smart city, connectivity is a key factor for its development. Therefore, we focus on analyzing themes and trends in the study of control, the smart city, and the small symbolic challenges posed by cable theft that enables interactivity in Medellín, from a critical accounting perspective. Copper cable theft is costly for telecommunications companies and society. The research shows a lack of control over losses of this asset, which are estimated between 83% and 98%. Methodologically, we conducted a documentary analysis to establish the main themes. Additionally, we performed a robustness and survival study to locate the events of theft and the spatial areas where they occur. Accounting databases were consulted to identify the increase in theft and the materialization of theft risk. These events are consistent with the critique of control from an accounting perspective.